Improving the photosensitizing properties of ruthenium polypyridyl complexes using 4-methyl-2,2′-bipyridine-4′-carbonitrile as an auxiliary ligand - Mecchia Ortiz, Juan Hugo (2013)
We report in this work the synthesis and spectroscopic, electrochemical, spectroelectrochemical, and photophysical characterization of a novel series of ruthenium polypyridyl complexes with 4-methyl-2,2′-bipyridine-4′- carbonitrile (Mebpy-CN) as an auxiliary ligand of general formula [Ru(bpy) 3-x(Mebpy-CN)x](PF6)2 (x = 1-3) (with bpy = 2,2′-bipyridine). A significant increase in the lifetime and quantum yield of emission of the lowest 3MLCT excited state is disclosed when going from x = 1 to x = 3, evidencing an improvement of the photosensitizing properties with respect to [Ru(bpy)3](PF 6)2. Furthermore, quenching by molecular oxygen of 3MLCT excited states of the three complexes produced singlet molecular oxygen (1O2) with quantum yield values higher than that of [Ru(bpy)3]2+ in CH3CN. The structure of the complex with x = 1 has been determined by X-ray diffraction. The photoconductivity of ZnO nanowires covered with this same complex is increased by an order of magnitude, pointing to its feasibility as a component of a DSSC. A new dinuclear complex with Mebpy-CN as a bridging ligand has also been prepared and characterized by physicochemical techniques. The derived mixed-valent species of formula [(bpy)2RuII(Mebpy-CN) RuIII(NH3)5]5+ displays a considerable metal-metal electronic coupling due to the delocalization effect of a nitrile group in the 4′ position of the bpy ring. © 2013 American Chemical Society.